8th RILEM International Conference on Mechanisms of Cracking and Debonding in Pavements - Chabot, Armelle; Buttlar, William G.; Dave, Eshan V.; Petit, Christophe; Tebaldi, Gabriele; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2016)
This book presents the latest advances in research to analyze mechanical damage and its detection in multilayer systems. The contents are linked to the Rilem TC241 - MCD scientific activities and the proceedings of the 8th RILEM International Conference on Mechanisms of Cracking and Debonding in Pavements (MCD2016). MCD2016 was hosted by Ifsttar and took place in Nantes, France, on June 7-9, 2016. In their lifetime, pavements undergo degradation due to different mechanisms of which cracking is among the most important ones. The damage and the fracture behavior of all its material layers as well as interfaces must be understood. In that field, the research activities aims to develop a deeper fundamental understanding of the mechanisms responsible for cracking and debonding in asphalt concrete and composite (e.g. asphalt overlays placed on PCC or thin cement concrete overlay placed on asphalt layer) pavement systems.
-- Adhesion Between Asphalt Layers Through the Leutner Shear Test, by Gaspar Matheus et al. -- Advanced Characterisation Methods for Interface Shear Resistance for Airport Overlays, by White Greg et al. -- Analysis of the draft European Standard on Interlayer Bonding and Understanding of the Influencing Factors, by Dony Anne et al. -- Comparative Analysis of Interlayer Bonding Behaviour of Different Types of Pavement Interfaces, by Freire Ana Cristina et al. -- Investigation of Bond between Asphalt Layers in Flexible Pavement, by Nguyen Ngoc Lan et al. -- Performance-based Test Regime for High Friction Surfacing Systems on Asphalt Pavements, by Wu Jeremy et al. -- Round Robin Tests on Reective Cracking Laboratory Tools, by Martin Antoine et al. -- The Effect of Interface Bonding Criterion on Pavement Design Reinforcement, by Loizos Andreas et al. -- Debonding Mechanisms (bituminous interface) -- Development of a pull-off test to measure the bond strength of bituminous emulsions, by Leprince Lucas et al. -- Debonding In Airfield Pavement Hot Mix Asphalt Layers, by Garg Navneet et al. -- Impact of new High Inflation Pressure Aircraft Tyres on Asphalt Overlay Interface Debonding, by White Greg -- Localized debonding as a potential mechanism for near-surface cracking, by Hernando David et al. -- Experimental evidence of the viscoelastic behavior of interfaces in bituminous pavements - An explanation to top-down cracking?, by Grellet Damien et al. -- Experimental Characterization of the Interface Damage between Bituminous Layers: from the Interphase to th.
Keywords: Building materials; Materials -- Analysis; Mechanics, Applied; Mathematics -- Data processing; Building Materials; Characterization and Analytical Technique; Engineering Mechanics; Computational Mathematics and Numerical Analysis